2015
DOI: 10.1002/pssr.201409401
|View full text |Cite
|
Sign up to set email alerts
|

Dual plasmonic-enhanced bulk-heterojunction solar cell incorporating gold nanoparticles into solution-processed anode buffer layer and active layer

Abstract: A dual plasmonic resonance effect on the performance of poly(3‐hexylthiophene) (P3HT):phenyl C61‐butyricacid methyl ester (PC61BM) based polymer solar cells (PSCs) has been demonstrated by selectively incorporating 25 nm colloidal gold nanoparticles (Au NPs) in a solution‐processed molybdenum oxide (MoO3) anode buffer layer and 5 nm colloidal Au NPs in the active P3HT:PCBM layer. The devices exhibit up to ∼20% improvement in power conversion efficiency which is attributed to the dual effect of localized surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Many inorganic nanoparticles and small molecules have been utilized to form composite with P3HT in OTFTs and higher charge carrier mobilities have been obtained successfully . Among these nanocomposite systems, P3HT/Au has been widely explored in numerous electronic devices . Our previous report demonstrated that the threshold voltage ( V th ) of P3HT‐based transistors was controllable regulated by utilizing gold nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
“…Many inorganic nanoparticles and small molecules have been utilized to form composite with P3HT in OTFTs and higher charge carrier mobilities have been obtained successfully . Among these nanocomposite systems, P3HT/Au has been widely explored in numerous electronic devices . Our previous report demonstrated that the threshold voltage ( V th ) of P3HT‐based transistors was controllable regulated by utilizing gold nanoparticles .…”
Section: Introductionmentioning
confidence: 99%